Efficacy and safety profile of minocycline in patients with urogenital chlamydia infection: results of an open randomized comparative clinical trial - Margarita R. Rakhmatulina (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. Urogenital chlamydia infections is a widespread STI, 131 million people are infected every year. Despite the absence of a reliable correlation with respect to antimicrobial resistance of chlamydia strains to tetracyclines, macrolides and fluoroquinolones in vitro and in vivo, scientists are studying the issue of reducing the sensitivity of the pathogen to traditionally used drugs and are investigating the effectiveness of antibacterial drugs active against Chlamydia trachomatis. One of the drugs with high anti-chlamydia activity is minocycline. Aims. To study the efficacy and safety of the minocycline (Minolexin®) in the treatment of urogenital chlamydia infection in comparison with the doxycycline (Unidox Solutab®). Methods. An open randomized comparative clinical trial included 100 patients: group 1 - 50 patients who received minocycline 100 mg 2 times a day for 7 days, group 2 - 50 patients who received doxycycline 100 mg 2 times a day in within 7 days. The diagnosis was confirmed by the detection of C. trachomatis by PCR. The parameter of the effectiveness of therapy was the eradication of C. trachomatis and the absence of clinical symptoms 4 weeks after therapy. Results. 1 week after therapy, clinical symptoms were registered in 20; 40.8% patients of group 1 and 28 (57.1%) patients of group 2 (p = 0.106), 4 weeks later - in 4; 8.2% patients of group 1 and 7 (18.4%) patients of group 2 (p = 0.524). In group 1, the absence of most subjective clinical symptoms was recorded in a shorter time than in the comparison group. 100% of patients had achieved eradication C. trachomatis, laboratory signs of an inflammatory reaction were recorded in 2 (5.0%) patients of group 1 and 3 (7.3%) patients of group 2 (p = 1,000). According to the frequency of adverse drug events, there were also no significant differences between the compared groups, however, in group 2 patients, adverse drug events that had a high probability of being associated with taking the drug were recorded more often than in the group of patients receiving minocycline. Conclusions. The results of the study demonstrated the comparable effectiveness of minocycline and doxycycline in the treatment of urogenital chlamydia infection and a similar safety profile of these drugs.